The Development of Instructional Multimedia For Teaching Speaking Using Experiential Learning Method For The Eighth Grade Students of Madrasah Tsanawiyah Miftahul Jannah Palangka Raya - Muhammad Rezeki (Lembaga Pengembangan Kinerja Dosen, 2025)
Learning process is designed to achieve graduation standard where the objective of teaching learning process is to develop student’s attitude, knowledge and skill competence. However, based on the preliminary observation, The problems frequently found in English Learning is that their native language causes them difficult to use the foreign language. The students are seldom to practice their speaking because they are afraid of making mistakes. Therefore, the students should actively involve in the learning process and understand about the material deeply. Regarding of those conditions, this study is intended to develop Instructional multimedia for teaching speaking using Experiential Learning Method. The subject of this research and development (R and D) was the eighth grade students of Madrasah Tsanawiyah Miftahul Jannah Palangka Raya. The research was accomplished through the procedures of need analysis, adoption of syllabus and lesson plans, first draft of instructional multimedia development, expert validation, media revision, media try out, and final product. The Research instruments used in this study are questionnaire, interview, and observation which were distributed to the students, teachers and also the expert validation. The data obtained were analyzed and explained qualitatively. The result of need analysis showed that the students and teachers required instructional multimedia which is relevant to their major content needs, interest, motivation, and Curriculum. Considering to the results, the multimedia was selected and adapted from Ministry of Education source, relevant school books, and appropriate websites. The important thing that the multimedia is focused to adopt the syllabus and lesson plans. The data collected from questionnaires, interview, and observation reflected that the students were very interested to learn speaking using Experiential Learning method and the teachers were in need and intended to adopt the instructional multimedia of teaching speaking using Experiential Learning method in their teaching speaking process. The Final Product in this research is in the form of video of teaching Speaking Using Experiential Learning Method for the eighth Grade students of MTs Miftahul Jannah Palangka Raya.